The legacy of Franco Basaglia: protection of Fundamental rights through deinstitutionalization and social participation (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The author emphasizes the implications in the field of Constitutional law, of the historical speech given by Franco Basaglia at the national Congress: Society and Mental Diseases which took place in Rome, from the 20th to the 22nd of June 1968. Two cornerstones in Basaglia’s approach are determinant: critics to Psychiatric asylums as oppressive institutions to ban and to overcome; communitarian solidarity and broad participation as the keys to establish and maintain a community based mental health network so to support effective fundamental rights for people with mental disorder.
Keywords: Deinstitutionalisation; Psychiatric Hospitals; Franco Basaglia; Community based health care; Constitutional rights